Research on inventory model degradation (Journal of Advances and Scholarly Researches in Allied Education, 2024)
As a result of its practical importance in sectors dealing with time-sensitive products, things vulnerable to obsolescence, and perishable commodities, the study of degrading inventory has attracted a lot of interest in operations and supply chain management. This research delves into the history of declining inventory models, specifically looking at how they have included different elements that affect declining inventory, such as changes in demand rates, lead times, pricing tactics, and environmental concerns. The study takes a look at both old and new models, analysing deterministic and probabilistic techniques, and hybrid methods that use fuzzy and stochastic variables to convey real-world uncertainty better. Important topics covered include the financial effects of degradation, the best way to place orders, and how technology can help with both management and prediction of degradation. The purpose of this research is to fill knowledge gaps in the current literature by proposing novel theoretical frameworks and modelling approaches to deal with complicated inventory dynamics, particularly under unstable and unpredictable market conditions.